Iodine/Chlorine Multi‐Electron Conversion Realizes High Energy Density Zinc‐Iodine Batteries - Jiajin Zhao; Yan Chen; Mengyan Zhang; Ziqi An; Binbin Nian; Wenfeng Wang; Hao Wu; Shumin Han; Yuan Li; Lu Zhang (Advanced Science)
Abstract Aqueous zinc‐iodine (Zn‐I2) batteries are promising energy storage devices; however, the conventional single‐electron reaction potential and energy density of iodine cathode are inadequate for practical applications. Activation of high‐valence iodine cathode reactions has evoked a compelling direction to developing high‐voltage zinc‐iodine batteries. Herein, ethylene glycol (EG) is proposed as a co‐solvent in a water‐in‐deep eutectic solvent (WiDES) electrolyte, enabling significant utilization of two‐electron‐transfer I+/I0/I− reactions and facilitating an additional reversibility of Cl0/Cl− redox reaction. Spectroscopic characterizations and calculations analyses reveal that EG integrates into the Zn2+ solvation structure as a hydrogen‐bond donor, competitively binding O atoms in H2O, which triggers a transition from water‐rich to water‐poor clusters of Zn2+, effectively disrupting the H2O hydrogen‐bond network. Consequently, the aqueous Zn‐I2 cell achieves an exceptional capacity of 987 mAh gI2−1 with an energy density of 1278 Wh kgI2−1, marking an enhancement of ≈300 mAh g−1 compared to electrolyte devoid of EG, and enhancing the Coulombic efficiency (CE) from 68.2% to 98.7%. Moreover, the pouch cell exhibits 3.72 mAh cm−2 capacity with an energy density of 4.52 mWh cm−2, exhibiting robust cycling stability. Overall, this work contributes to the further development of high‐valence and high‐capacity aqueous Zn‐I2 batteries.